PENGARUH ECONOMIC VALUE ADDED, MARKET VALUE ADDED DAN FINANCIAL DISTRESS TERHADAP VOLATILITAS STOCK RETURN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING - Jaunanda, Meiliana; Sembel, Roy; Hulu, Edison; Ugut, Gracia Shinta S. (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract. This study was conducted to effect of economic value added, market value added, altman zscore, and corporate social responsibility on volatility Stock Return. Samples were taken from companies that conducted an Initial Public Offering on the Indonesia Stock Exchange from 2018 to 2020 using a purposive sampling method, thus obtaining sample data of 71 companies. Data will be tested using data panel eviews10 program. The results of this study indicate that (1) Economic Value Added have negative effect and no significant effect on Stock Return , (2) Market Value Added have negative effect and no significant effect on Stock Return, (3) Altman Zscore have negativeÂ effect and significant effect on Stock Return, (4) Corporate Social Resposibility have negativeÂ effect and significant effect on Stock Return, (5) Corporate Social Resposibility have memoderate economic value added on Stock Return , (6) Corporate Social Resposibility have memoderate market value added on Stock ReturnAbstrak. Penelitian ini menguji pengaruh economic value added, market value added, altman zscore, dan corporate social responsibility terhadap volatilitas likuiditas saham. Sampel diambil dari perusahaan yang melakukan Initial Public Offering di Bursa Efek Indonesia dari tahun 2018 sampai dengan tahun 2020 dengan menggunakan metode purposive sampling, sehingga diperoleh data sampel sebanyak 71 perusahaan. Data akan diuji menggunakan program data panel eviews10. Hasil penelitian ini menunjukkan bahwa (1)Economic Value Added berpengaruh negatif dan tidak signifikan terhadap likuiditas saham, (2)Market Value Added berpengaruh negatif dan tidak signifikan terhadap likuiditas saham, (3)Altman Zscore berpengaruh negatif dan berpengaruh signifikan terhadap likuiditas saham, (4)Corporate Social Resposibility berpengaruh negatif dan signifikan terhadap likuiditas saham, (5)Corporate Social Resposibility dapat memoderasi economic value added terhadap likuiditas saham, (6) Corporate Social Resposibility dapat memoderasi market value added terhadap likuiditas saham